The Impact of Baby Massage to Sleep Quality on Baby Age of 3-6 Months at Work District Puskesmas II Denpasar Timur. - Matalia, Ni Putu Ike Windari (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Sleep is an important factor and influences the baby growth and development. Sleep requirement isn’t only viewed from quantity aspect but quality as well. With good sleep quality, baby’s growth and development can be achieved optimally. One of the options to increase the baby’s sleep quality is by applying the baby massage. The aim of this research is to know the impact of baby massage to sleep quality on baby age of 3-6 months at work district of Puskesmas II Denpasar Timur. The method which is used in this research is pre-experimental study ( one group pre-test dan post-test design) with Wilcoxon Signed Rank Test . The sample is totally 30 samples without control group, gathered by purposive sampling technique. Collecting data uses baby sleep questionnaire. The result is 80% of babies have good sleep quality and 20% moderate sleep quality. Mean point of the sample before massaged is 23,77, whereas mean point of the sample after massaged is 30,83. The result of data analysis shows there is an impact of the baby massage to sleep quality on baby age of 3-6 months at work district Puskesmas II Denpasar Timur ( Asymp. ? value  point 0,000 (? ? 0,05 ) ).
Keywords: Baby Massage, sleep quality, Baby Age of 3-6 Months